Integrity of pipelines transporting hydrocarbons corrosion, mechanisms, control, and management - Bolzon, Gabriella (NATO Science for peace and security series C: environmental security, 2011)
This book describes technical and practical aspects of pipeline damage. It summarizes the phenomena, mechanisms and management of pipeline corrosion in-service. The topics discussed include pipelines fracture mechanics, damage mechanisms and evolution, and pipeline integrity assessment. The concept of acceptable risk is also elucidated and the future application of new knowledge management tools is considered.